The Karaskan Sayyids Of Ferghana: An Archival Exploration Of A Saintly Family - Mirzaeva, Maftuna (CV. Inara, 2024)
Saintly families played a crucial role in the socio-political life of Central Asia, making their study an innovative direction in family studies within the region. The archives of these saintly families have been explored through examples of some well-known families. The main problem in this study is exploration of Karaskan sayyids archive. This work focuses on the Karaskan sayyids, a prominent sayyid family in the Ferghana valley, with a particular emphasis on their family archive. At present, only a part of the family’s documents, specifically copies, have been examined. My research aims to delve into the historical documents related to this family, which are dispersed across various locations. The fate of the Karaskan sayyids post-19th century remains largely unknown, a gap that has not been addressed in the limited studies available on this family. By meticulously analyzing these documents, my project seeks to reconstruct the family archive and illuminate the subsequent history of the Karaskan sayyids. This study not only contributes to our understanding of the socio-political dynamics of Central Asia but also highlights the significance of archival research in uncovering the histories of influential families. Finding of the research provide a clearer picture of the Karaskan sayyids’ archive and their impact on the region.